Reticulocyte Binding Protein Homologue 5 is a target of balancing selection in the Plasmodium falciparum population of Papua New Guinea - Naung, Myo T.; Martin, Elijah; Wong, Wilson; Razook, Zahra; Utama, Digjaya; Guy, Andrew J.; Harrison, Shannon Takala; Cowman, Alan F.; Lin, Enmoore; Kiniboro, Benson; Laman, Moses; Mueller, Ivo; et al. (Frontiers in Parasitology, 2023)
Plasmodium falciparum Reticulocyte Binding Protein Homologue (RH5), a leading malaria vaccine candidate, is essential for erythrocyte invasion by the parasite, interacting with the human host receptor, basigin. RH5 has a small number of polymorphisms relative to other blood-stage antigens, and in vitro studies have shown that vaccine-induced antibodies raised against RH5 are strain-transcending, however most studies investigating RH5 diversity have been done in Africa. Understanding the genetic diversity and evolution of malaria antigens in other regions is important for their validation as vaccine candidates. In this study the rh5 gene was sequenced in 677 samples from a longitudinal cohort of Papua New Guinean (PNG) children aged 1-3 years. Of 677 samples successfully sequenced, 566 were identified as independent infections (i.e. one of each pair of identical sequences within hosts were removed). A total of 14 non-synonymous polymorphisms were identified, eight that are ‘common’ in the population (minor allele frequency > 1%), with 44 haplotypes ranging in frequency from 1% to 21%. Modelling of common SNPs to the cryo-EM structure of the RH5/CyRPA/RIPR complex mapped them to the Basigin binding site and near the contact point of CyRPA. Tajima's D analyses of the corresponding nucleotide sequences produced positive values indicating potential hotspots of balancing selection. We attempted to confirm whether these signals were due to immune selection by measuring the rate of polymorphism between independent infections within the same host, and the association with clinical symptoms, however, no such associations were identified. Together these results suggest that whilst there is evidence of balancing selection driving RH5 diversity in the PNG P. falciparum population, immune escape was not observed within the cohort of young children. Limited immunity and therefore low selective pressure may explain this result, alternatively other evolutionary forces may contribute to balancing selection at the RH5-BSG binding interface in PNG.